Awareness on Sexual Abuse among Adolescents in Baglung District of Nepal - Sharma, Anita; Magar, Kamala Rana (Janapriya Journal of Interdisciplinary Studies, 2018)
Sexual abuse is a pervasive public health problem that affects all directly or indirectly causing many short- and long-term struggles for victims, families, communities and the whole social system. Although sexual abuse is growing as a major problem in community, especially among the adolescents the trend and facts have not been explored adequately. Therefore, a descriptive study entitled "Awareness on Sexual Abuse among Adolescents" was carried out among 114 students of grade 9 and 10 in Tribhuvan Secondary School at Baglung Municipality. Census method was adopted and self-administered structured questionnaire was used for data collection. Data was analyzed using SPSS Version 16. Descriptive and inferential statistics were used to analyze the data. The findings revealed, almost 51 percent had low level of awareness on sexual abuse, and prevalence rate of sexual abuse was 18.4 percent. Out of 114 respondents, 38.6 percent were of age 14 years and 66.7 percent of the respondents were studying in grade 10. The highest proportion 38.6 percent were Brahmin and 71.0 percent got information about sexual abuse from their teachers. More than half (59.6%) respondents define try to rape as a sexual abuse. There was significant association between education of respondents with awareness on sexual abuse. It is concluded that the awareness on sexual abuse is low among adolescents therefore there is need of awareness program and education to adolescents in the school and community for improving their knowledge as well as to make them aware of sexual abuse.